Trends in contraceptive demands and unmet need for family planning in migrant population of Uttarakhand - Singh, Sadhna; Priya, Neha; Roy, Debabrata; Srivastava, Anurag; Kishore, Surekha (International Journal Of Community Medicine And Public Health, 2018)
Background: The knowledge of contraceptive use and unmet need is important to know the constraints for unmet need based on user perspective. The aim of the study was to find the prevalence of Contraceptive use, Contraceptive preferred and the Un-met demand for contraceptives. Methods: Married, non-pregnant women of reproductive age group (15-49 years) from the migrant population were interviewed by Census method using pre-designed and pre-tested instrument by cross-sectional survey. Operational definitions for unmet need for spacing, limiting and unfelt need used in the study were as per NFHS -4 findings and traditional methods of contraception like abstinence, withdrawal were included in Un-met need for contraceptive due to its very high failure rate. Results: 58.44% study subjects had ‘Ever Used FP’ and 56.78% are currently using FP methods. The CPR is 56.7% by ‘Any Method’ and 43.0% by ‘Modern method’. The method which is most popular is ‘Sterlisation 29% and 20.96% and ‘Others’ i.e. highly unreliable methods like coitus interruptus, calendar method etc. found high number of users. The reasons for non use were apprehension of complication/side effects in 39%) and inconvenience or the difficulties with modern contraceptive methods or lack of knowledge by 7.67% and 6.95% respectively, 16% were relied on traditional methods, such as periodic abstinence, withdrawal and herbal mixtures from traditional healers as well as LAM 8% for a FP method, all of which have high failure rate. Only 24.8% Women were decision maker regarding the time and type of contraceptive to be used. The unmet need was 29.7% out of which the unmet needs for spacing and limiting were 9.6 per cent and 20.1 per cent, respectively Conclusions: The unmet need is high and can be addressed by removing the constraints such as poor accessibility to the knowledge thus removing apprehension for side effects, improve accessibility to resources and low decision-making autonomy.